Clinical features of cutaneous graft-versus-host disease in the bone-marrow transplanted leukemic child. - Schiera, A.; Beneggi, M.; Bozzato, N.; Arrigo, C.; Galbiati, G. (European Journal of Pediatric Dermatology, 2018)
Graft-versus-host-disease (GVHD) is a serious complication caused by immunologically competent cells from a donor. These cells recognize and react against "foreign" tissue antigens of an immunodeficient host who is unable to reject them, and cause a clinical syndrome involving particularly the skin and the liver. Two clinical variants of the disease have been described: the acute, which usually is observed within 60 days after a bone-marrow transplant, and the chronic form, which generally appears after 100 days and usually, but not always, follows acute GVHD. In this article, we present the clinical course of both the acute and chronic phases in two young patients who received a bone marrow transplant for leukemia in the Pediatric Department of the S. Gerardo Hospital in Monza. Furthemore, we report the incidence and clinical features of GVHD in 129 patients who received a bone marrow transplant in our hospital between 1985 and 1996.